FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN KONSERVATISME PADA PERUSAHAAN MANUFAKTUR DI BEI - OKTOMEGAH, CALVIN (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Management has options in choosing the method of accounting to produce financial statements in accordance with the conditions of their respective companies. In an effort to produce financial statements, one of the principle adopted is conservatism. Conservatism is the prudential principle which if implemented would result in the figures tend to be low income and assets. Conservatism is influenced by several factors, namely debt covenants, bonus plan, and political cost. This study aims to determine the factors that affect the application of conservatism. The study design is the object of research is quantitative and manufacturing industries listed in Indonesia Stock Exchange in the year 2008-2010 which was chosen by purposive sampling technique. Source data obtained from the Indonesia Stock Exchange. Data analysis was performed with multiple linear regression analysis. The results showed that the debt covenants and political costs have a positive influence on conservatism. Meanwhile, the bonus plan has no effect on conservatism. This is because the bonus plan which is represented by structure of managerial ownership in companies in Indonesia are relatively small, so it does not affect the application of conservatism.